2021
DOI: 10.1111/jog.14852
|View full text |Cite
|
Sign up to set email alerts
|

Our anesthesia experiences in COVID‐19 positive patients delivering by cesarean section: A retrospective single‐center cohort study

Abstract: Aim: Pregnancy increases susceptibility to respiratory complications of viral diseases. This study aims to evaluate our anesthesia practices in pregnant women with COVID-19 undergoing cesarean section. Methods: A total of 61 patients who underwent cesarean section and had positive Polymerase chain reaction (PCR) testing for COVID-19 with nasopharyngeal swabs were included in the study. Patient demographics and information about anesthesia were analyzed retrospectively from the patient medical files. Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Our study findings seem to support this assumption when viewed in combination with pre‐pandemic UK data [22]. The regional anaesthesia rate for caesarean birth in our study was higher than reported in studies from the USA (91.3%) [13], Europe (75%) and France (72%) [20, 21], and comparable with a small single‐centre study from Turkey (95%) [32]. Accordingly, the GA rate for caesarean section was lower in our sample than in other studies [13, 20, 21].…”
Section: Discussionsupporting
confidence: 90%
“…Our study findings seem to support this assumption when viewed in combination with pre‐pandemic UK data [22]. The regional anaesthesia rate for caesarean birth in our study was higher than reported in studies from the USA (91.3%) [13], Europe (75%) and France (72%) [20, 21], and comparable with a small single‐centre study from Turkey (95%) [32]. Accordingly, the GA rate for caesarean section was lower in our sample than in other studies [13, 20, 21].…”
Section: Discussionsupporting
confidence: 90%
“…An increased risk of preterm delivery and fetal compromise has been described in pregnancies complicated with COVID-19. 1,[19][20][21] The majority of pregnant women in the study were in their third trimester, and approximately one-third of them delivered preterm. Importantly, our study supports that preterm delivery and low birth weight are associated with maternal COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, in a study conducted in India on 115 patients, 5 cases were admitted to the ICU, out of which 1 patient (0.87%) died on the seventh postoperative day [ 31 ]. On the other hand, in a study including 61 COVID-19 positive cesarean deliveries in Turkey [ 32 ], in which 58 (95.1%) underwent spinal anesthesia, 1 case was admitted to the ICU after delivery under spinal anesthesia, she was intubated later on, and received mechanical ventilation for 68 days, after which she was discharged from the ICU 108 days after her admission. Among the three remaining patients who received general anesthesia, one patient was already intubated at the ICU due to respiratory worsening preoperatively, and she died on the tenth day of ICU follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three remaining patients who received general anesthesia, one patient was already intubated at the ICU due to respiratory worsening preoperatively, and she died on the tenth day of ICU follow-up. Based on these findings, Karasu et al, concluded that the mortality rate was 1.6% in all patients, 5.0% in symptomatic patients, and 11.1% in patients with pneumonia [ 32 ]. In the current study, the only mortality case was mainly related to the patient’s pre-operative respiratory condition.…”
Section: Discussionmentioning
confidence: 99%